The Incidence, Risk Factors and In-Hospital Mortality of Acute Kidney Injury in Patients After Surgery for Acute Type A Aortic Dissection: A Single-Center Retrospective Analysis of 335 Patients - Li, Linji; Zhou, Jiaojiao; Hao, Xuechao; Zhang, Weiyi; Yu, Deshui; Xie, Ying; Gu, Jun; Zhu, Tao (Frontiers in Medicine, 2020)
Abstract Background: Acute kidney injury (AKI) is a common complication of cardiac surgery, which could lead to increased morbidity and mortality. Acute type A aortic dissection (AAAD) is a life-threatening cardiac disease and can be closely related to postoperative AKI. However, data on the incidence of AKI defined by the newest Kidney Disease: Improving Global Outcomes (KDIGO) criteria and in-hospital mortality of a homogeneous population who underwent AAAD are limited. We aimed to investigate the incidence of AKI defined by the KDIGO criteria and the risk factors associated with the outcomes among AAAD-induced AKI patients. Methods: We reviewed 335 patients who underwent surgical treatment for AAAD between March 2009 and June 2016. We screened the patients' AKI status and analyzed probably risk factors of AKI and in-hospital mortality. Independent-Samples T test or Chi-square test was performed to identify differences between AKI and non-AKI groups, survivors with AKI and non-survivors with AKI, respectively. The logistic regression model was applied to identify independent risk factors. Results: AKI occurred in 71.94% of AAAD patients, including 85 stage 1 (35.26%), 77 stage 2 (31.95%), and 79 stage 3 (32.78%) patients. The in-hospital mortality rate was 21.16%. Logistic regression analysis showed that the body mass index, chronic kidney disease, chronic liver disease, cardiopulmonary bypass duration, red blood cell transfusion, and hypoproteinemia were the independent significant risk factors of the occurrence of postoperative AKI. The risk factors associated with in-hospital mortality among AAAD-induced AKI patients included AKI stage (odds ratio [OR] 3.322), deep hypothermic circulatory arrest (OR 2.586), lactic acidosis (OR 3.407), and continuous renal replacement therapy (OR 3.156). Conclusion: For AAAD patients undergoing surgery, AKI was a common complication and it increased patients’ mortality risk. Therefore, identifying the risk factors of AKI and preventing postoperative AKI are important for improving the postoperative outcomes of AAAD patients. Trial registration: ChiCTR, ChiCTR1900021290. Registered 12 February 2019, http://www.chictr.org.cn/showproj.aspx?proj=35795